Test‐retest reproducibility of neurochemical profiles with short‐echo, single‐voxel MR spectroscopy at 3T and 7T. Issue 4 (26th October 2015) - Terpstra, Melissa; Cheong, Ian; Lyu, Tianmeng; Deelchand, Dinesh K.; Emir, Uzay E.; Bednařík, Petr; Eberly, Lynn E.; Öz, Gülin
Abstract : Purpose: To determine the test‐retest reproducibility of neurochemical concentrations obtained with a highly optimized, short‐echo, single‐voxel proton MR spectroscopy (MRS) pulse sequence at 3T and 7T using state‐of‐the‐art hardware. Methods: A semi‐LASER sequence (echo time = 26–28 ms) was used to acquire spectra from the posterior cingulate and cerebellum at 3T and 7T from six healthy volunteers who were scanned four times weekly on both scanners. Spectra were quantified with LCModel. Results: More neurochemicals were quantified with mean Cramér‐Rao lower bounds (CRLBs) ≤20% at 7T than at 3T despite comparable frequency‐domain signal‐to‐noise ratio. Whereas CRLBs were lower at 7T ( P < 0.05), between‐session coefficients of variance (CVs) were comparable at the two fields with 64 transients. Five metabolites were quantified with between‐session CVs ≤5% at both fields. Analysis of subspectra showed that a minimum achievable CV was reached with a lower number of transients at 7T for multiple metabolites and that between‐session CVs were lower at 7T than at 3T with fewer than 64 transients. Conclusion: State‐of‐the‐art MRS methodology allows excellent reproducibility for many metabolites with 5‐min data averaging on clinical 3T hardware. Sensitivity and resolution advantages at 7T are important for weakly represented metabolites, short acquisitions, and small volumes of interest. Magn Reson Med 76:1083–1091, 2016. © 2015 Wiley Periodicals, Inc.